The Prevalence of Iron Deficiency in Atrial Fibrillation: Low Hanging Fruit? - Bachar Alabdullah; David Ferreira; Erin Bourke; Harish Kamalanathan; Ibrahim Elashri; Kushal Porwal; Michael J. Tiller; Payal H. Gadre; Sarah Jones; Michael McGee (Medicina, 2022)
Background and Objectives: Atrial fibrillation (AF) is the most common sustained arrhythmia worldwide. The relationship between AF and iron deficiency is poorly understood. Materials and Methods: We conducted an observational study investigating the prevalence of iron deficiency in those with AF. Iron deficiency was defined by the American College of Cardiology (ACC) criteria for iron deficiency in heart failure. Results: Of 134 eligible subjects, 81 (60.4%) met the ACC definition of iron deficiency in heart failure. Those who were iron deficient were more likely to be female (OR 1.876, p = 0.005), have a history of diabetes mellitus (OR 3.085, p = 0.001) a history of stroke (OR 3.147, p = 0.016), and have higher CHA2DS2-VASc (p ≤ 0.0001) and Charlson Comorbidity Index scores (CCI) (p = 0.007). Conclusions: The prevalence of iron deficiency in those with AF appears high and warrants evaluation in a prospective study.